The Curious Human Knee - Yu, Han (Columbia University Press, 2023)
Distilling a vast amount of research in a style that is engaging, conversational, and even personal and witty, this book opens readers' eyes to the complexity and significance of the humble knee
Description based on publisher supplied metadata and other sources
Keywords: Knee-Diseases